PENDAMPINGAN PENGEMASAN DAN PELABELAN UMKM â€œJAMU POJOK BANGKAâ€ UNTUK PENINGKATAN DAYA SAING EKONOMI - Lestari, Ning Puji; Sutarsi; Purbasari, Dian; Taruna, Iwan (Jurnal Abdi Insani, 2024)
Herbal drinks are a significant part of Indonesiaâ€™s cultural heritage, made from various spices and renowned for their health benefits, including refreshing the body, speeding up metabolism, and increasing appetite. One of the local small and medium enterprises (UMKM), â€œJamu Pojok Bangka,â€ supplies herbal medicine retailers in Jember District. However, these herbal drinks were previously sold in used mineral water bottles, lacking proper labels, making them less appealing and unhealthy for consumers. To address this issue, a service was initiates to enhance economic competitiveness. This service provides assistance to ensure that herbal medicine products meet packaging and labeling standards. This service is carried out by two methods, namely lectures and training. The lecture method is carried out at the beginning to provide an understanding of how to package products well. Furthermore, training methods are carried out related to the production process, packaging selection, packaging process, and labeling design. The packaging solutions were tailored based on different sales methods: 1.5 L glass or HDPE bottles for mobile sales and 250 mL labeled PET plastic bottles for retail sales. To evaluate the effectiveness of the new packaging, consumer attractiveness testing was carried out. This involved comparing herbal drink sales with the old and new packaging. The results clearly demonstrated that the new packaging significantly increased consumer appeal and preference. This improvement not only enhances the productâ€™s marketability but also contributes to preserving Indonesiaâ€™s rich cultural heritage.